2017
DOI: 10.1002/mdc3.12451
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Brain Atrophy in Alternating Hemiplegia of Childhood

Abstract: Background Alternating hemiplegia of childhood (AHC) is a rare neurodevelopmental disorder that includes involuntary movements, paroxysmal symptoms, and various severities of nonparoxysmal symptoms. Objective To investigate the occurrence of structural brain abnormalities in patients with AHC during clinical courses. Methods Conventional brain magnetic resonance imaging findings and clinical courses were retrospectively investigated in 14 patients with AHC confirmed by ATP1A3 mutations. Results Progressive fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…In ATP1A3 ‐related disorders, brain MRI abnormalities are not generally detected. However, as we previously reported, 14 some patients with typical AHC show mild cerebellar cortical atrophy in adulthood. The cerebellar atrophy detected by brain MRI in both cases of the current study is similar to the atrophy previously reported in typical patients with AHC and the c.2401G>A (p.Asp801Asn) variant or c.2423C>T (p.Pro808Leu) variant in ATP1A3 14 .…”
Section: Discussionsupporting
confidence: 63%
“…In ATP1A3 ‐related disorders, brain MRI abnormalities are not generally detected. However, as we previously reported, 14 some patients with typical AHC show mild cerebellar cortical atrophy in adulthood. The cerebellar atrophy detected by brain MRI in both cases of the current study is similar to the atrophy previously reported in typical patients with AHC and the c.2401G>A (p.Asp801Asn) variant or c.2423C>T (p.Pro808Leu) variant in ATP1A3 14 .…”
Section: Discussionsupporting
confidence: 63%
“…Histological analysis revealed no evidence of neurodegeneration in young Atpα mutants, but CJ10/+ and DTS2/+ flies aged to median lifespan exhibited loss of brain tissue, indicated by the accumulation of vacuolar and spongiform-like neuropathology in the central brain and optic lobe, in contrast to the minimal neuropathology seen in aged WT controls (Palladino et al, 2003;Ashmore et al, 2009). Thus, neurodegeneration in these Atpα mutants appears to be age dependent, paralleling the progressive brain atrophy observed in AHC patients (Saito et al, 1998;Sasaki et al, 2017).…”
Section: Fruit Fly (Drosophila Melanogaster)mentioning
confidence: 83%
“…Among 87 patients with AHC, 60% exhibited resting electrocardiogram (ECG) abnormalities ( Balestrini et al, 2020 ). Whether AHC is a progressive disorder remains unclear, but a study of 94 patients with AHC detected mild worsening of motor and intellectual disability with age ( Uchitel et al, 2021 ), while abrupt stepwise deterioration ( Sasaki et al, 2014 ) and progressive brain atrophy ( Saito et al, 1998 ; Sasaki et al, 2017 ) in AHC patients have also been reported. The most common AHC-causing mutations in ATP1A3 are D801N, E815K and G947R ( ), of which E815K has the most severe phenotype ( Sasaki et al, 2014 ; Yang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our case did not have obvious ataxic symptoms despite the long duration of the disease, but the brain MRI revealed cerebellar atrophy. Actually, one case report reported atypical AHC cases with ataxic phenotype and cerebellar atrophy, 5 and rapid onset ataxia is another ATP1A3 -related disorder. 6 7 Therefore, the cerebellar atrophy of this patient is another example of atypical manifestation of AHC.…”
Section: Discussionmentioning
confidence: 99%